Pengembangan Media Pembelajaran Display Board Berbasis Discovery Learning Pada Tema 6 Subtema 2 Kelas V SD Negeri 040452 Kabanjahe T.A 2022/2023 - Natasyah Br Sitepu; Apiek Gandamana (Journal on Education, 2023)
This study aims to determine the validity that is validated by the media validator, material validator, and test instrument validator, find out practicality by teacher education practitioners and students, and find out the effectiveness as seen from the results of the pre-test post-test scores on display board learning media based on discovery learning on theme 6, sub-theme 2 class V at SD Negeri 040452 Kabanjahe, the number of which is 25 people. This research is research and development which leads to the ADDIE development model which consists of 5 stages, namely the analysis, design, development, implementation, and evaluation stages. Based on the results of the research, the display board media developed showed results, including: (1) The results of the validity by each validator obtained the final results of media validation with a percentage score of 92% (Very Eligible), material validation with a percentage score of 90.66% (Very Eligible). Feasible), test instrument validation with a percentage score of 94% (Very Feasible). (2) The results of practicality by teacher education practitioners obtained results with a percentage score of 96% (Very Practical), the results of the overall response of students obtained results of 82.4% (Very Practical). (3) The results of the effectiveness through the pre-test post-test obtained the final score with a percentage of 88% (Very Effective). After obtaining the overall results of research and development, the researcher drew the conclusion that discovery learning-based display board learning media is valid, practical, and effective in the teaching process in schools.